Research on the Influence of Organization-based Self-Esteem on New Generation Employees’ Innovative Behavior Based on SEM - Hang Liu, Wen Xu (Forest Chemicals Review)
Based on conservation of resource theory, this study regards organization-based self-esteem as personal resources, exploring the influence mechanism of organization-based self-esteem on the new generation employees’ innovative behavior from the perspective of resource function. The research utilizes SPSS25.0 and Mplus8.3 to analyze 325 two-stage questionnaire survey data from 25 Chinese enterprises, and the main effect and mediating effects are tested by using the structural equation model. The results of the empirical analysis indicate that organization-based self-esteem has significant positive effects on innovative behavior, and work engagement mediates the relationship between organization-based self-esteem and innovative behavior. Therefore, the study provides a reference for better managing the new generation employees’ innovation behavior.